Optimization Design of a Kind of Compliant Constant Force Mechanism - Lu, Shuaishuai; Zhang, Xiao; Wang, Shulin; Wang, Fei; Zhang, Zhiming; Chen, Jun; Li, Anqing; Luan, Fuyu; Zhu, Zhiyong (Conference proceedings (International Conference on Manipulation, Manufacturing and Measurement on the Nanoscale. Online), 2024)
Compliant constant force mechanism has the characteristic of outputting constant force. In this article, the optimization design method of a kind of parallel compliant constant force mechanism is studied. The approach utilizes finite element analysis in conjunction with a multi-objective genetic optimization algorithm (MOGA) as its foundation. It is segregated into two processes: Firstly, the theoretical analysis process of the constant force mechanism is introduced. The mechanism is composed of a double V beam and a bistable beam in parallel. The double V beam provides positive stiffness, and the bistable beam provides negative stiffness. After determining the constant force characteristics and initial design parameters, the multi-objective genetic algorithm (MOGA) based on the finite element analysis results is used to optimize the model. It is verified by finite element simulation that the optimized model can have a large constant force stroke. The finite element simulation results show that compared with the initial structure, the constant force stroke of the optimized compliant constant force mechanism (CFM) is increased by 60%.